2013
DOI: 10.3177/jnsv.59.367
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects on the Liver and Pancreas Resulting from Maternal Vitamin D Restriction in Mice

Abstract: SummaryThis study aimed to investigate the effects of maternal vitamin D restriction on carbohydrate metabolism and alterations in the pancreas and liver in the F1 and F2 generations. Therefore, we studied the first two generations of offspring (F1 and F2) of Swiss mice from mothers fed one of two diets: SC (standard chow) or VitD 2 (vitamin D-deficient). Biometric, biochemical and molecular analyses were performed. The VitD-F1 mice had greater body mass (BM) than the SC-F1 mice. The BM changes were accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Interestingly, in males submitted to HF diet, we observed higher insulin plasma level, glycemia, HOMA IR and insulin resistance, as previously reported in control conditions. 24,[32][33][34] Surprisingly, in females, no perturbation of the glucose homeostasis was observed. At the opposite, VDD-HF females displayed similar values as CTRL-LF or VDD-LF for several parameters, including insulinemia, glycemia, and HOMA-IR.…”
Section: F I G U R Ementioning
confidence: 92%
“…Interestingly, in males submitted to HF diet, we observed higher insulin plasma level, glycemia, HOMA IR and insulin resistance, as previously reported in control conditions. 24,[32][33][34] Surprisingly, in females, no perturbation of the glucose homeostasis was observed. At the opposite, VDD-HF females displayed similar values as CTRL-LF or VDD-LF for several parameters, including insulinemia, glycemia, and HOMA-IR.…”
Section: F I G U R Ementioning
confidence: 92%
“…In one of the earliest transgenerational mouse vitamin D fetal programming studies, compared with controls, 6-month-old F1 generation offspring of VDD dams displayed greater body and epididymal fat mass (Nascimento et al 2013). These mice also had increased insulin secretion when given an oral glucose challenge and showed marked hepatic steatosis.…”
Section: Rodent Modelsmentioning
confidence: 99%
“…More recently, it has been shown that a grand-maternal (F0) high-fat diet in the mouse has the opposite effect, with an increase in pancreatic mass and islet density persisting to the F2 generation (Graus-Nunes et al 2015 ). In a mouse model of grand-maternal vitamin D deficiency, not only the size of pancreatic islets, but also the amount of steatosis present in the liver of the F2 generation was affected by the transgenerational exposure (Nascimento et al 2013 ). However, in order to have a direct effect on the structure and function of organs in the F2 generation, it is not sufficient for the F1 generation merely to have structural alterations in organs such as the pancreas and liver.…”
Section: Introductionmentioning
confidence: 99%